An explanatory case study on cloud computing applications in the built environment - Chong, Heap Yih; Wong, J.; Wang, Xiangyu (Elsevier BV, 2014)
Fragmentation of practices is one of the key issues in the built environment. However, with advances in Information and Communication Technology (ICT), particularly cloud computing, the fragmentation of working practices can be potentially overcome. The technology could enhance communication and information flowin various stages along a project life cycle.Due to the increasing demands and the newly developed cloud computing applications, it is critical to review and identify the appropriate cloud computing applications in the built environment. A total of forty two cloud computing applications consisting of general cloud applications, Building Information Modelling (BIM), and project management cloud applications were selected and critically reviewed. A decision-making model was also developed to assist parties in selecting a suitable application. The explanatory case study has discovered numerous possible cloud computing applications in various disciplines, for example, Google Apps, Autodesk BIM 360, and Viewpoint are the applications with the most features. The findings contribute to creating a certain awareness and an insight to reduce the fragmented working practices in the built environment.